A silole copolymer containing a ladder-type heptacylic arene and naphthobisoxadiazole moieties for highly efficient polymer solar cells. Issue 2 (9th January 2015) - Zhang, Zhiyun; Lin, Francis; Chen, Hsieh-Chih; Wu, Hung-Chin; Chung, Chin-Lung; Lu, Chien; Liu, Shih-Hung; Tung, Shih-Huang; Chen, Wen-Chang; Wong, Ken-Tsung; Chou, Pi-Tai
Abstract : We present a silole ladder-type copolymer, PSiNO, with a high molecular weight that affords a remarkable PCE of 8.37%. Abstract : We report a combination of a silole containing ladder-type heptacylic arene and naphthobisoxadiazole moieties for highly efficient polymer solar cells. This new class of PSiNO polymer possesses a planar, rigid backbone and a low-ordering framework. This unique feature facilitates chain extension, leading to high hole mobility and hence a high PCE of 8.37% without further thermal annealing.